Social Capital and Prosocial Behavior among German Children - Helen Barton; Jared Thorpe; Mikaela Dufur (Social Sciences, 2020)
A robust literature connects children’s and adolescents’ social capital to a range of desirable outcomes, including increased academic achievement and decreased delinquency. We extend this research by extending possible associations with child social capital to positive behaviors, measured here as prosocial behaviors. We examine data on 6th graders in Germany. We select the German context in part because one important source of child social capital, participation in religious congregations, is not as prevalent in modern Germany as in the US samples from which many social capital studies are derived. We use data from the German National Educational Panel Study (NEPS) and measures of child social capital, including parent–child interactions, family activities, and religious participation, to predict prosocial behavior. Results indicate that social capital in the form of parent-child interactions in the home and child religiosity is associated weakly with greater prosocial behavior. These results suggest that adults can help children develop stronger prosocial norms by increasing interaction with their children and by exposing their children to network ties in religious settings, but also that social capital can be derived different ways in different contexts.